RELATIONSHIP OF AND ATTITUDE WITH CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) IN THE COMMUNITY IN U BARO VILLAGE COT GIREK DISTRIC NORTH ACEH - Komala Kartikasari Nst; Mahruri Saputra; Fazilla Ash Syifa (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The importance of clean and healthy living behavior (PHBS) in the household is that every household can improve their health and not get sick easily, children grow up healthy and intelligent, work productivity of family members increases. Clean and healthy living behavior (PHBS) is an action that is produced based on awareness and is partly an effort to become a person/group to improve themselves in the health sector. One of the efforts made to improve health is by providing health education so that people are healthy and free from various diseases. The aim of this research is to determine the relationship between knowledge and attitudes and clean and healthy living behavior (PHBS) in the community in U Baro village, Cot Girek subdistrict, North Aceh district. The instrument used in this research was a questionnaire. This research uses quantitative research with a correlational design with a cross sectional approach. This research was carried out on 29 - 2 August 2023. The total sample was 92 respondents. The sampling technique used purposive sampling. Data analysis in this study used the chi square test, the results of the study showed that there was a relationship between knowledge and clean and healthy living behavior with a p value of 0.006 < 0.05, which means there is a significant relationship between knowledge and clean and healthy living behavior, it can be seen that there is The relationship between attitude and clean and healthy living behavior has a p value of 0.003<0.05, which means there is a significant relationship between attitude and clean and healthy living behavior><0.05, which means there is a significant relationship between attitude and clean and healthy living behavior.